The humanities : cultural roots and continuities. V.1 : Cultural roots - Witt, Mary Ann Frese; ... [et al.] (Boston : Houghton Mifflin, 1997)
This book is about: Earliest civilizations; The Greco-Roman and Judeo-Christian roots; Medieval cultures; The West African cultural root; ...
Keywords: Civilization; Western civilization; Civilization, Western -- History; Civilization, Western -- History -- Sources; Humanities; Africa -- Civilization; Africa -- Civilization -- Sources